Relasi Sosial Pimpinan Tradisional Minangkabau dalam Mengatasi Dampak Sosial Panambangan Emas Ilegal di Nagari Ranah Batahan - Rido, Muhammad Rasyid; Nurdin, M.Fadhil; A. Rachim, Hadiyanto (Jurnal Sosiologi Andalas, 2025)
The Minangkabau Traditional Leadership, which consists of traditional leaders, religious leaders and intellectual leaders, has an important role in maintaining social balance and resolving various problems in the community. In the midst of rampant illegal gold mining in the Batahan Region which has triggered various social impacts, these traditional leaders face big challenges in maintaining community stability and prosperity. The aim of this research is to describe social relations between traditional Minangkabau leaders and identify the obstacles faced in overcoming the social impacts of illegal gold mining. Using the theoretical framework of Robert K. Merton's Structural Functional Theory, a qualitative approach was applied through observation, in-depth interviews and documentation with ten informants. Data was analyzed through a process of data reduction, data display, and conclusion verification. The research results show that traditional leaders build relationships with Dalihan Na Tolu, KAN (Kerapatan Adat Nagari), Wali Nagari, and Jorong Chiefs; religious leaders liaise with Ulil Amri (umaro), the Indonesian Ulama Council (MUI), and the Office of Religious Affairs (KUA); as well as intellectual leaders interacting with social religious organizations and non-governmental organizations. This relationship strengthens synergy in overcoming the social impacts of illegal gold mining. Obstacles faced include a lack of government support, community non-compliance, and economic challenges that encourage illegal mining. Apart from that, differences in views and lack of coordination between stakeholders also hamper the effectiveness of response efforts. The synergy of traditional Minangkabau leadership has proven effective in mitigating negative impacts, but requires further support. Recommendations include increasing the capacity of traditional leaders, closer collaboration with the government for better law enforcement, and community education to achieve sustainable solutions.